The specific features of phononic and magnetic subsystems of type-VII clathrate EuNi2P4. Issue 32 (5th August 2020) - Novikov, V. V.; Bud'ko, S. L.; Matovnikov, A. V.; Mitroshenkov, N. V.; Pilipenko, K. S.; Konoplin, N. A.; Plokhikh, I. V.; Pfitzner, A.; Shevelkov, A. V.
Abstract : EuNi2 P4 clathrate with a Eu 2+ guest embedded into a Ni–P framework, was synthesized by a two-stage synthesis, confirmed to crystallize in the orthorhombic space group Fddd, unit cell parameters a = 5.1829(1) Å, b = 9.4765(1) Å, and c = 18.9900(1) Å. Abstract : A type-VII clathrate with a Eu 2+ guest embedded into a Ni–P covalent framework, EuNi2 P4, was synthesized by a standard two-stage ampoule synthesis and confirmed to crystallize in the orthorhombic space group Fddd with unit cell parameters a = 5.1829(1) Å, b = 9.4765(1) Å, and c = 18.9900(1) Å. A general technique for studying the lattice and magnetic properties of REE containing compounds is proposed. The temperature and field dependences of electrical resistivity ρ ( T, H ), magnetization M ( T, H ), magnetic susceptibility χ ( T, H ), heat capacity C p ( T ), and unit cell parameters a ( T ), b ( T ), c ( T ), and volume V ( T ) were experimentally studied and analyzed at different pressures in the temperature range of 2–300 K. A cascade of anomalies in the studied dependences was identified and attributed to the magnetic phase transformation and peculiar lattice contributions at temperatures below 20 K. As a result of comparison with an isostructural clathrate SrNi2 P4, the parameters of the magnetic and lattice contributions were determined. It is characteristic that the phase transition from the paramagnetic to the magnetically ordered state is not reflected in the temperature changes of the lattice parameters due to weak bonds between guest europium atoms and the Ni–P host matrix. We have constructed a tentative H – T phase diagram based on the M ( T ) and M ( H ) data, which includes 6 different phases. It is established that the anomalous lattice contribution to the clathrate heat capacity C TLS ( T ) appears due to the effect of two-level systems (TLS) in the Eu 2+ subsystem on the thermodynamic properties of EuNi2 P4 . The values of TLS parameters as well as the parameters of the magnetic subsystem of the clathrate were determined.